1268. Efficacy, safety, and tolerability of bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in adults with HIV-HBV infection - preliminary results. (15th December 2022) - Kwakwa, Helena; Bran, Jacqueline; Ruff, Julia; Choe, Sunny; Chua, Joel V
Abstract: Background: Coinfection with HIV and hepatitis B (HBV) has been associated with higher risk of morbidity and mortality, especially acceleration of liver disease. HBV-active antiretroviral (ARV) regimens have significantly improved the outcome of people with HIV-HBV coinfection. B/F/TAF has been shown to be highly effective in the treatment of HIV infection based on treatment naïve and switch trials. Although it is an HBV-active regimen, there is scant data on the use of B/F/TAF for people with HIV-HBV coinfection. We hypothesize that B/F/TAF is both safe and efficacious in the treatment of coinfected adults. Methods: This open label, single-arm, switch study enrolled HIV/HBV-coinfected adults from two clinical centers (Baltimore, MD and Philadelphia, PA). Patients were switched from their current ARV regimen (regardless of viral suppression) to fixed dose combination B/F/TAF taken once daily for 48 weeks. Primary efficacy endpoints were proportion of patients with HIV RNA < 50 copies/mL by FDA Snapshot Algorithm and HBV DNA < 29 IU/mL at Week 24 by missing = failure method. Results: A total of 28 eligible participants were enrolled between May 2019 to December 2021. Median age was 51 years (range 34-71), majority were Black (89%), male gender (86%), and non-Hispanic (96%), 65% HIV and HBV virally suppressed. Two participants, one lost to follow-up and the other removed due to non-adherence prior to week 24, were excluded in the efficacy analysis. At baseline, 73% were HIV suppressed and 81% were HBV suppressed. Of the 21 patients with week 24 data, 20 (95%) had HIV RNA < 50 copies/mL and 19 (90%) had HBV DNA < 29 IU/mL. Eighteen (86%) were HIV and HBV suppressed, which was higher than prior to B/F/TAF use. There were ten treatment-related adverse events (AE), all of which were mild (grade 1) and transient. Most common treatment related AE was nausea (2 of 28). Four patients had elevated alanine aminotransferase at baseline, all of which normalized at week 24. There were no serious adverse events or hepatitis flare. No participants discontinued study treatment due to an AE. Conclusion: B/F/TAF is efficacious and safe for patients coinfected with HIV and HBV after 6 months of treatment. Disclosures: Helena Kwakwa, M.D., Viiv Healthcare: Grant/Research Support Sunny Choe, PhD, Gilead Sciences: Employee.